MANAJEMEN KRISIS PERSPEKTIF AL-QUR'AN DAN HADIS - Rahayu, Sri; Ahmadi, Ahmadi; Hidayati, Noorazmah (CV. Lafadz Jaya, 2024)
This article discusses the concept of crisis management in Islam through analysis of hadith with sanad and matan as well as support from verses from the Koran. The hadith which says,